2017
DOI: 10.1021/acsami.6b15018
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly Engineered Azobenzene Derivatives for High Energy Density Solid-State Solar Thermal Fuels

Abstract: Solar thermal fuels (STFs) harvest and store solar energy in a closed cycle system through conformational change of molecules and can release the energy in the form of heat on demand. With the aim of developing tunable and optimized STFs for solid-state applications, we designed three azobenzene derivatives functionalized with bulky aromatic groups (phenyl, biphenyl, and tert-butyl phenyl groups). In contrast to pristine azobenzene, which crystallizes and makes nonuniform films, the bulky azobenzene derivative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 44 publications
(76 reference statements)
4
85
0
Order By: Relevance
“…S25 ). From all of these experiments, we concluded that the observed exotherm in Z -AzoPMA 3 is associated with discharging, is exclusively from the isomerization of the Z -isomer to the E -isomer, and is consistent with observations made by others 2 , 3 , 22 24 . We thus used AzoPMA 3 for the remainder of our studies.…”
Section: Resultssupporting
confidence: 91%
“…S25 ). From all of these experiments, we concluded that the observed exotherm in Z -AzoPMA 3 is associated with discharging, is exclusively from the isomerization of the Z -isomer to the E -isomer, and is consistent with observations made by others 2 , 3 , 22 24 . We thus used AzoPMA 3 for the remainder of our studies.…”
Section: Resultssupporting
confidence: 91%
“…To put this value into context it is interesting to compare it to other valid MOST candidates, based for example on azobenzene derivatives. Promising solid MOST materials based on neat azobenzenes have been reported, with energy density up to about 100 kJ kg −1 (and 88 kJ mol −1 ); liquid azobenzene derivatives have also been made, reaching a gravimetric energy density of 115 kJ kg −1 . The energy density of the reported system a translates to a possible adiabatic temperature rise of 384 °C, underlining the potential of this class of compounds for MOST applications.…”
Section: Discussionmentioning
confidence: 97%
“…While these ones are mostly based on the norbornadiene‐quadricyclane system, other molecular entities have also been proposed . Herein, the azobenzene represents a highly potent candidate as there is longstanding experience in studying this system as a dye as well as a molecular switch . The storage energy of a given MOST system is based on the energy differrence between two states.…”
Section: Figurementioning
confidence: 99%
“…[3] Herein, the azobenzene represents a highly potent candidate as there is longstanding experience in studying this system as a dye as well as a molecular switch. [7,8] The storage energy of a given MOST system is based on the energy differrence between two states. In case of the azobenzene, this is the (E)-isomer as the lower energy state and the (Z)-isomer as the metastable high-energy state ( Figure 1).…”
mentioning
confidence: 99%